2016
DOI: 10.1002/ijc.29990
|View full text |Cite
|
Sign up to set email alerts
|

Stress management by autophagy: Implications for chemoresistance

Abstract: Development of chemoresistance, which limits the efficiency of anticancer agents, has long been a major problem in cancer therapy and urgently needs to be solved to improve clinical outcomes. Factors contributing to chemoresistance are various, but a key factor is the cell's capability for stress management. Autophagy, a favored survival strategy that organisms employ to get over many kinds of stress, is emerging as a crucial player in drug resistance. It has been shown that autophagy facilitates the resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 150 publications
(269 reference statements)
5
70
1
Order By: Relevance
“…Previous reports indicated that antitumor drug administration results in an increase in HMOX1 expression in tumor cells, which might be a pro‐survival mechanism linked to the induction of autophagy . This suggests that autophagy is induced in tumor cells treated with antitumor drugs and is, thereby, involved in acquired resistance to chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that antitumor drug administration results in an increase in HMOX1 expression in tumor cells, which might be a pro‐survival mechanism linked to the induction of autophagy . This suggests that autophagy is induced in tumor cells treated with antitumor drugs and is, thereby, involved in acquired resistance to chemotherapy …”
Section: Discussionmentioning
confidence: 99%
“…In chaperone-mediated autophagy the substrates have a pentapeptide lysosome-targeting motif (KFERQ) that is recognized by a complex of chaperone proteins and target the complex to lysosomal membrane. Given that autophagy has been linked to inhibit several diseases, like neurodegeneration, diabetes and infectious diseases as well as promotion of some cancer especially chemoresistance (as reviewed in [28], [29] and [30]); the linkages between ER stress and autophagy may also have relevance to several of these diseases.…”
Section: Autophagymentioning
confidence: 99%
“…Autophagy plays a critical role in evolutionarily conserved cellular degradation process, providing materials and energy for cell metabolism under certain stress, such as oncogenic stress or cancer drug stress [11]. The role of autophagy in chemoresistance should be under intense investigation.…”
Section: Introductionmentioning
confidence: 99%